2019
DOI: 10.1016/j.ophtha.2018.09.043
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness Analysis of Adalimumab for the Treatment of Uveitis Associated with Juvenile Idiopathic Arthritis

Abstract: Objectives:To investigate the cost-effectiveness of adalimumab in combination with methotrexate, compared with methotrexate alone, for the management of uveitis associated with Juvenile Idiopathic Arthritis (JIA-U).Design: A cost-utility analysis based on a clinical trial and decision analytic model. Participants: Children and adolescents aged 2 to 18 years with persistently active JIA-U, despite optimized methotrexate treatment for at least 12 weeks. Methods: The SYCAMORE trial [ISRCTN10065623] of methotrexat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(41 citation statements)
references
References 20 publications
0
41
0
Order By: Relevance
“…2). The costs reported by studies from European countries [1,7,14,17,18,27] were considerably higher than those reported by other regions [4,15,20,26] (Table 1).…”
Section: Information On Jia Costsmentioning
confidence: 78%
See 2 more Smart Citations
“…2). The costs reported by studies from European countries [1,7,14,17,18,27] were considerably higher than those reported by other regions [4,15,20,26] (Table 1).…”
Section: Information On Jia Costsmentioning
confidence: 78%
“…1). Eleven were economic studies [1,7,[14][15][16][17][18][19][20][21][22], three retrospective observational [23][24][25] and four cohorts [4,[26][27][28].…”
Section: Selection Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Hughes et al reported that in the United Kingdom, adalimumab does not currently represent a cost-effective treatment option for the public health system. 31 Other authors, however, opposed the conclusions of the study, contesting the methodology used and emphasizing the lack of therapeutic options in cases of resistance to methotrexate, with the same clinical efficacy as adalimumab. 32 , 33 In the present review, only one study (Ramanan 2017 21 ) reported data on quality of life and the cost-effectiveness of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Re: Saeedi et al: Agreement and predictors of discordance of 6 visual field progression algorithms (Ophthalmology. 2019;126:822e828) TO THE EDITOR: We read with interest the article by Saeedi et al 1 The authors tested 6 methods to detect glaucomatous visual field (VF) progression on a large cohort of glaucomatous patients: mean deviation (MD) rate, Visual Field Index (VFI) rate, pointwise linear regression, permutation analyses of the pointwise linear regression, the Collaborative Initial Glaucoma Treatment Study scoring system, and the Advanced Glaucoma Intervention Study scoring system. They found poor to moderate intermethod agreements with only about 6% of eyes labeled as progressing by the majority of the methods.…”
mentioning
confidence: 99%